Liver Injury, Endotoxemia, and Their Relationship to Intestinal Microbiota Composition in Alcohol‐Preferring Rats. (29th October 2018) - Posteraro, Brunella; Paroni Sterbini, Francesco; Petito, Valentina; Rocca, Stefano; Cubeddu, Tiziana; Graziani, Cristina; Arena, Vincenzo; Vassallo, Gabriele A.; Mosoni, Carolina; Lopetuso, Loris; Lorrai, Irene; Maccioni, Paola; et al.
Abstract : Background: There is strong evidence that alcoholism leads to dysbiosis in both humans and animals. However, it is unclear how changes in the intestinal microbiota (IM) relate to ethanol (EtOH)‐induced disruption of gut–liver homeostasis. We investigated this issue using selectively bred Sardinian alcohol‐preferring (sP) rats, a validated animal model of excessive EtOH consumption. Methods: Independent groups of male adult sP rats were exposed to the standard, home‐cage 2‐bottle "EtOH (10% v/v) versus water" choice regimen with unlimited access for 24 h/d (Group Et) for 3 (T1), 6 (T2), and 12 (T3) consecutive months. Control groups (Group Ct) were composed of matched‐age EtOH‐naïve sP rats. We obtained samples from each rat at the end of each experimental time, and we used blood and colon tissues for intestinal barrier integrity and/or liver pathology assessments and used stool samples for IM analysis with 16S ribosomal RNA gene sequencing. Results: Rats in Group Et developed hepatic steatosis and elevated serum transaminases and endotoxin/lipopolysaccharide (LPS) levels but no other liver pathological changes (i.e., necrosis/inflammation) or systemic inflammation. While we did not find any apparent alteration of the intestinal colonic mucosa, we found that rats in Group Et exhibited significant changes in IM composition compared to the rats in Group Ct. These changes were sustained throughout T1, T2, and T3. In particular, Ruminococcus, Coprococcus, and Streptococcus were the differentially abundant microbial genera at T3. The KEGG Ortholog profile revealed that IM functional modules, such as biosynthesis, transport, and export of LPS, were also enriched in Group Et rats at T3. Conclusions: We showed that chronic, voluntary EtOH consumption induced liver injury and endotoxemia together with dysbiotic changes in sP rats. This work sets the stage for improving our knowledge of the prevention and treatment of EtOH‐related diseases.